The Chemistry of Marine Sponges(∗) - Ebada, Sherif S. (Handbook of Marine Natural Products, 2012)
Marine sponges continue to attract wide attention from marine natural product chemists and pharmacologists alike due to their remarkable diversity of bioactive compounds. Since the early days of marine natural products research in the 1960s, sponges have notoriously yielded the largest number of new metabolites reported per year compared to any other plant or animal phylum known from the marine environment. This not only reflects the remarkable productivity of sponges with regard to biosynthesis and accumulation of structurally diverse compounds but also highlights the continued interest of marine natural product researchers in this fascinating group of marine invertebrates. Among the numerous classes of natural products reported from marine sponges over the years, alkaloids, peptides, and terpenoids have attracted particularly wide attention due to their unprecedented structural features as well as their pronounced pharmacological activities which make several of these metabolites interesting candidates for drug discovery. This chapter consequently highlights several important groups of sponge-derived alkaloids, peptides, and terpenoids and describes their biological and/or pharmacological properties.